A biomarker of oxidative stress as a nontraditional risk factor in obese subjects. (August 2013) - Vassalle, Cristina; Vigna, Luisella; Bianchi, Sara; Maffei, Silvia; Novembrino, Cristina; De Giuseppe, Rachele; de Liso, Federica; Vannucci, Alessandro; Tirelli, Silvia; Maiavacca, Rita; Bamonti, Fabrizia
Background: Oxidative stress has been postulated as an additive factor linking obesity to cardiovascular disease.Materials & methods: Derivatives of reactive oxygen species metabolites (d-ROMs) were measured in 136 obese (42 males, 94 females; mean age: 47 ± 12 years; BMI: 36 ± 5 kg/m 2 ) and in 306 over- and normal-weight subjects (112 males, 194 females; age: 47 ± 12 years; BMI: 24 ± 3 kg/m 2 ).Results: d-ROMs levels were higher in obese than in over- and normal-weight subjects (395 ± 104 vs 362 ± 102 and 351 ± 84 arbitrary units (AU); p < 0.001), in women than males (390 ± 104 vs 327 ± 68 AU; p < 0.001), in subjects with than those without hypertension (390 ± 103 vs 360 ± 95 AU; p < 0.01) and in smokers than former and nonsmokers (380 ± 97 vs 358 ± 97 AU; p < 0.05). A positive correlation was found between d-ROMs and BMI (r = 0.25; p < 0.001) and age (r = 0.13; p < 0.01). Levels of d-ROM (>75th percentile: 420 AU) remained as an independent obesity predictor (odds ratio: 2.5; p < 0.001) in women. Continuous variables are reported as mean ± standard deviation.Conclusion: d-ROMs are a powerful obesity predictor, and could represent a reliable tool in obesity and cardiovascular risk evaluation, especially in women.